MODEL PENCIPTAAN PENGALAMAN WISATA YANG BERKESAN UNTUK MENINGKATAN INTENSI LOYALITAS WISATAWAN KAWASAN WISATA GEOPARK DI PROVINSI JAWA BARAT - Riski Taufik Hidayah, - (2022)
Two Geopark areas in West Java Province have an internationally worthy geological heritage, as well as diverse and important biodiversity and cultural heritages. The presence of Geopark status in the two areas is expected to be able to increase the number of tourists so that they can contribute to economic development in the area. However, the COVID-19 pandemic caused the sector to experience a decline as a consequence of the government's efforts to reduce the outbreak through closing and opening up tourist areas so that the tourism sector suffered serious monetary losses as seen from the decline in tourist visits. This research examines the model of creating memorable tourist experiences to increase the intensity of tourist loyalty in Geopark Tourism Areas in West Java Province. Thus, the purpose of this research is to analyze the effect of the attribute destination and the image destination on memorable tourist experiences and their interactions with the intensity of tourist loyalty in the Geopark Tourism Area in West Java. This research used a quantitative approach, while the type of research carried out in this research were descriptive and verification research used exploratory survey methods. The population in this research were tourists who had visited the Geopark Tourism Area in West Java. The sampling technique used in this research was probability sampling with the proportioned stratified sampling method with a minimum number of samples researched as many as 311 respondents. The descriptive analysis used were cross tabulation analysis and the percentage of achievement scores for each indicator, dimension, and variable. While the verification analysis used the structural equation model analysis method used the SmartPLS statistical application. The results of the research show that there is a direct influence given by the attribute destination and the image destination on an impressive tourist experience, as well as a memorable tourist experience that is able to mediate between the attribute destination and the image destination on the intention of tourist loyalty. This research resulted in a finding of a model for increasing loyalty intentions through the creation of memorable tourist experiences in the Geopark Tourism Area. The findings of the model in this research are named "The Model of Increasing Loyalty Intention of Geopark Tourist Areas" which is the novelty of the results of this research.